The Associations between Regional Gray Matter Structural Changes and Changes of Cognitive Performance in Control Groups of Intervention Studies - Takeuchi, Hikaru; Taki, Yasuyuki; Sassa, Yuko; Sekiguchi, Atsushi; Nagase, Tomomi; Nouchi, Rui; Fukushima, Ai; Kawashima, Ryuta (Frontiers in Human Neuroscience, 2015)
In intervention studies of cognitive training, the challenging cognitive tests, which were used as outcome measures, are generally completed in more than a few hours. Here, utilizing the control groups’ data from three 1-week intervention studies in which young healthy adult subjects underwent a wide range of cognitive tests and T1-weighted magnetic resonance imaging (MRI) before and after the intervention period, we investigated how regional gray matter (GM) density (rGMD) of the subjects changed through voxel-based morphometry (VBM). Statistically significant increases in rGMD were observed in the anatomical cluster that mainly spread around the bilateral dorsal anterior cingulate cortex (dACC) and the right superior frontal gyrus (rSFG). Moreover, mean rGMD within this cluster changes were significantly and positively correlated with performance changes in the Stroop task, and tended to positively correlate with performance changes in a divergent thinking task. Affected regions are considered to be associated with performance monitoring (dACC) and manipulation of the maintained information including generating associations (rSFG), and both are relevant to the cognitive functions measured in the cognitive tests. Thus, the results suggest that even in the groups of the typical “control group” in intervention studies including those of the passive one, experimental or non-experimental factors can result in an increase in the regional GM structure and form the association between such neural changes and improvements related to these cognitive tests. These results suggest caution toward the experimental study designs without control groups.